Heterogeneity and self-referentiality in Things Fall Apart’s proverbs - Lombardo, Andrea Laura (Moderna Språk, 2018)
This article aims to provide a revisiting of the novel Things Fall Apart (1958) by the Nigerian essayist and writer Chinua Achebe (1930-2013) as regards the established notion in postcolonial studies which claims that African literature solely writes back to the western paradigm. The central thesis of this paper is that Achebe’s seminal first novel exhibits self-referential moments as do metafictional texts of the 1990s (Mwangi, 2009) to particularly focus on local nuances as well as colonial criticism. This self-reflexive technique foregrounds aspects of content and form that are especially evident in the use of proverbs. In this sense, we attempt to assess the significance of the internal heteroglossia staged in proverbs which venture unexplored thresholds between the “self” and the “other” and enact a new aesthetics characterized by the umbrella of minor literatures (Deleuze and Guattari [1975] 1986; Bensmaïa, 2017). Proverbs as locus of such hybridization (Bhabha, 1994) and heterogeneity grant a space for the “other” in the Anglophone narrative and also allow the deconstruction of the notion of “other” for African purposes. In a complementary fashion, our concern will be to explore how this heterogeneity is reproduced in the three Spanish translations done by Jorge Sarrió (1966), Fernando Santos (1986) and José Manuel Álvarez Flórez (1997), all of them published in Spain. Accordingly, we approach the analysis of interlingual heterogeneity (Spoturno, 2010) founded on an operation of deterritorialization (Deleuze and Guattari, [1975] 1986) by comparing how the Spanish translators have rendered these configurations of heterogeneity and hybridity present in the original proverbs into the translated texts and, at the same time, by accounting for the strategies used for their recreation (Bandia, 2006; Tymoczko, 1999; Murphy, 2010).